Student Affairs in Canada in 2013 Perceptions, Trends, and an Outlook toward the Future - Browne, Jennifer; Speed, David Thomas Alan; Walker, Lilly (Canadian Journal of Higher Education, 2015)
Chief Student Affairs Officers (CSAOs) are senior-level student affairs personnel. In 2011, 33 CSAOs responded to a national survey and provided a professional perspective on field development, student services, as well as predicted five-year trends for student affairs. In 2013, 17 CSAOs responded to the same survey and provided further information on these topics. Results indicated that attitudes towards diversity and technology remained stable between 2011 and 2013. We established that CSAOs have less positive attitudes towards research, evaluation, and assessment than they do towards communication and leadership. Here, we discuss at length the implications of these finding, as well as the potential for research into student affairs. In addition, we examine the continued professionalization of the CSAO field and note that research into CSAOs should be proactive instead of reactive.